PERANCANGAN SISTEM INFORMASI PENGARSIPAN SURAT MASUK DAN KELUAR BERBASIS WEB DI SMK MUHAMMADIYAH 1 PADANG - Harianto, Dimas; Mary, Thomson; Nurdin, Bernediv (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The current development of information technology has had a significant impact on improving the performance of various agencies, both private and public, at SMK Muhammadiyah 1 Padang, the process of managing letters in schools is still carried out manually, so that there are often recording errors, difficulties in searching archives, and wasting time and money.The research method used is observation, interviews and documentation to obtain the needs of the system. The system development method uses software development life cycle (SDLC) with a waterfall model with stages of planning, analysis, design, testing and implementation. The system is built using the laravel framework, MySQL, PHP, HTML, and CSS.The alpha test results showed that it worked well based on the whitebox and blackbox tests, and the beta test results from experts showed an average of 96.33% and from users showed an average of 87.18%, from the expert testing and users got excellent information. This system is expected to improve the archiving of digital letters accurately, safely, and efficiently at SMK Muhammadiyah 1 Padang.